Structural characterization and thermal behaviour of block copolymers of polydimethylsiloxane and polyamide having trichlorogermyl pendant groups - Gill, R.; Mazhar, M.; Siddiq, M. (John Wiley & Sons, 2010)
Block copolymers having a pendant trichlorogermyl group as a part of polyamide segment-(CO-R'-CO-NH-Ar-NH-)(x)CO-R'-CO-and polydimethylsiloxane of general formula [(-CO-R'-CO-HN-Ar-NH)(x)-CO-R'-CO-NH(CH(2))(3)SiO(CH(3))(2) ((CH(3))(2)SiO)(y)Si(CH(3))(2)(CH(2))(3) NH-](n) (where R' = CH(2)CH(GeCl(3)), CH(CH(3)) CH(GeCl(3)), CH(GeCl(3)) CH(CH(3)); Ar = C(6)H(4), (-C(6)H(3)-CH(3))(2), (-C(6)H(3)-OCH(3))(2), 2,5-(CH(3))(2)-C(6)H(2), C(6)H(4)-O-C(6)H(4)) were prepared by a polycondensation reaction and characterized using CHN and Ge analysis, Fourier transform infrared (FTIR) and (1)H NMR spectroscopy, thermogravimetric analysis (TGA) and molecular weight determination. They have a lamellar structure with weight-average molecular weight in the range 1.21x10(5)-4.79x10(5) gmol(-1). These copolymers display two glass transition temperatures and have anaverage decomposition temperature of 489 degrees C. TGA, FTIR and gas chromatography/mass spectrometry studies indicate that degradation of these block copolymers results in carbon monoxide, oligomeric siloxanes and polyamide fragments. They are thermally stable due to the hydrogen bonded interlinked chains of polyamide, while they absorb water due to the presence of Ge-Cl bonding. (C) 2010 Society of Chemical Industry